Bangladesh baseline surveys on child labour situation in Bidi Industry in Kushtia, Tangail, and Rangpur districts - Karim, A.H.M Zehadul; Ali Islam, M. Zulfiquar; Farrukh, Md. Omar (International Labour Office Dhaka, 2004)
The International Programme on the Elimination of Child Labour (IPEC) of the International Labour Organization (ILO) has been working in a collaborative effort with the government, workers' and employees' and organizations, and civil society to prevent and eliminate child labour and its worst forms worldwide. As part of its endeavour, Bangladesh has also been striving to address the child labour issue through government, workers' and employers' organizations, NGOs and other international organizations with the launching of an action-oriented US Department of Labor (USDOL) funded Project titled "Preventing and eliminating the worst forms of child labour in selected formal and informal sectors". This research is a part of it.